Clinical Evaluation of a Metagenomics-Based Assay for Pneumonia Management - Zhan, Yangqing; Xu, Teng; He, Fusheng; Guan, Wei-jie; Li, Zhengtu; Li, Shaoqiang; Xie, Mingzhou; Li, Xiaolei; Chen, Rongchang; Cheng, Linling; Zhong, Nanshan; Ye, Feng (Frontiers in Microbiology, 2021)
Clinical value of metagenomic next-generation sequencing (mNGS) in pneumonia management is still controversial. A prospective study was conducted to evaluate the clinical impact of PneumoSeq in 57 immunocompetent (ICO) and 75 immunocompromised (ICH) pneumonia patients. The value of PneumoSeq for both etiological and clinical impact investigation in pneumonia was assessed. Among the 276 potential pathogens detected with PneumoSeq in our cohort, 251 (90.9%) were cross-validated. Clinical diagnoses of the causative pathogens were obtained for 97 patients, 90.7% of which were supported by PneumoSeq. Compared to conventional testing, PneumoSeq suggested potentially missed diagnoses in 16.7% of cases (22/132), involving 48 additional pathogenic microorganisms. In 58 (43.9%) cases, PneumoSeq data led to antimicrobial treatment de-escalation (n=12 in ICO, n=18 in ICH) and targeted treatment initiation (n=7 in ICO, n=21 in ICH). The PneumoSeq assay benefited the diagnosis and clinical management of both ICH and ICO pneumonia patients in real-world settings.